Chácara do Rosário: um estudo do patrimônio cultural no âmbito do turismo rural de Itu-SP - Pessoa, Mara Aristeu (Universidade Federal de São Carlos, 2010)
The present work has as main objective to analyze the current uses of the historical-cultural heritage in the development of tourist activities in a historic farm in the Itu region: Chácara do Rosário. For that, it started from the theoretical-conceptual discussion about rural tourism, cultural heritage, the relationship between heritage and tourism, and the use of cultural goods according to economic and social development. It was possible to understand that heritage would be an important attraction capable of motivating visitors with tourist activities that provide direct or indirect contact with cultural goods. The case study of Chácara do Rosário included appraisals on horseback riding, built heritage and cultural heritage maintenance issues. We sought to analyze tourist activities and elements of dissemination that would use heritage as the main support for economic development via tourism.
Chácara do Rosário: a study of cultural heritage in the field of rural tourism in Itu-SP
Keywords: Turismo no espaço rural; Patrimônio; Chácara do Rosário; Rural tourism; Heritage; CIENCIAS SOCIAIS APLICADAS::TURISMO